Exploring the Phenomenon of Joint Leadership: The Case of French-Azerbaijani University, Dual Degree Program in Azerbaijan - Mirzayeva, Leyla (ADA University, 2021)
This study aims to explore the phenomenon of joint leadership by learning the experience of two leaders and the perceptions of staff and faculty working together in a multicultural team in an educational institution; to find out attributes, benefits, and challenges, as well as communication, negotiation, decision-making process carried out within joint leadership; and to contribute to the development of dual degree programs in terms of management. Since joint leadership is new for Azerbaijan, the desired level of research has not been conducted in the literature. In this sense, it is considered important to add the deficiencies of the research in the literature. This research is important in terms of contributing to the theory and practice of joint leadership that might be required in the Azerbaijani context. The target population and sample size of the study consists of 2 leaders, 2 staff, and 2 faculty members. To collect the primary data, semi-structured interviews were used. Research findings imply that joint leadership can be considered as a leadership approach in which two or more employers are involved in managerial actions and processes, and managerial decisions, take an active role and experience mutual relationship and interaction among employees. One of the benefits of joint leadership is that it involves sharing the work among the group members and thus doing it based on the interaction of more than one leader. Relational difficulties between leaders are considered one of the main challenges of joint leadership.
Keywords: Education; Joint leadership.; Higher education.; Leadership.; Dual degree program -- Higher education.